Analysis of the Development of Gender Stereotypes and Sexist Attitudes Within a Group of Italian High School Students and Teachers: A Grounded Theory Investigation - Francesco Sulla; Barbara Agueli; Andreana Lavanga; Maria Grazia Mada Logrieco; Stefania Fantinelli; Ciro Esposito (Behavioral Sciences)
Gender stereotypes and sexist attitudes continue to persist in educational settings, with significant implications for students’ achievement and well-being. This study aimed to investigate the development of gender stereotypes and sexist attitudes among Italian high school students and trainee teachers. A series of focus groups were conducted with a group of Italian school students and trainee teachers to uncover the complex interplay of individual, interpersonal, institutional, and societal factors that contribute to the formation and perpetuation of these biases. Analysis was conducted using a grounded theory approach. The findings reveal a nuanced and multifaceted understanding of the issue, highlighting the critical role of teacher attitudes, peer influence, and broader cultural norms in shaping students’ perceptions and behaviors. This study offers insights for educators, policymakers, and researchers seeking to address gender inequities in education and promote more inclusive and equitable learning environments.